Penerapan model pembelajaran cooperative script untuk meningkatkan kemampuan membaca pemahaman pada kelas v sekolah dasar - Abdini, Rivenski; Winarni, Retno; Yulianti, Yulianti (Universitas Sebelas Maret, 2019)
Abstract. The purpose of this research was to improve comprehension reading ability, through used Cooperative Script learning model for 5th grade of elementary school student at Surakarta on 2018/2019. This study was a classroom action research. The subjects of this study were class teacher and 32 students from 5th grade of elementary school student. The procedure of this research consisted of 2 cycle, each cycle consisted of 2 learning process. Data collection of this research was done by interviewing, observing, comprehension reading ability testing, and documenting technique. The data’s validity in this research was done by using content validity, source triangulation, and tecnique triangulation. Qualitative data of this research were analysed throught use analysis interactif model (Miles and Huberman), while quantitative data of this research were analysed throught use descriptive comparative model. The classical average value of student’ comprehension reading ability test increased from the first cycle to the second cycle. The classical average of the first cycle was 73,41 (59,4%), it increased to 79.84 (84,4%) in the second cycle. Based on the result of this study, it concluded that Cooperative Script learning model could increase the comprehension reading ability of 5th grade of elementary school student.Keyword: comprehension reading ability, cooperative script learning model, elementary school